A giant mucinous borderline neoplasm of the mesentery misdiagnosed as an adnexal cyst – a case report and literature review. Issue 1 (2017) - Barani, Tomas; Gotseva, Mihaela; Polson, Alexander; Nath, Rahul; Mehra, Gautam; Lane, Geoff; Sayasneh, Ahmad
No abstract available